New Terahertz Laser Lines From (13)CD(3)OH Pumped by Regular and Hot Bands CO(2) Laser - Moretti, A.; Moruzzi, G.; Strumia, F.; Moraes, João Carlos Silos [UNESP]; Carelli, G. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
We have used our new pulsed CO(2) laser, operating both on regular and hot bands, to excite the (13)CD(3)OH methanol isotopomer. This has lead to the observation of 13 new high-threshold far-infrared laser emissions (also identified as terahertz laser lines), with frequencies in the range between 24.11 and 102.56 cm(-1) (0.72-3.07 THz). The absorption transitions leading to these new FIR laser emissions have been located by observing the optoacoustic absorption spectra around the CO(2) emissions. Here, we present these new far-infrared laser lines, characterized in wavelength, polarization, offset relative to the center of the pumping CO(2) laser transition, relative intensity, and optimum operation pressure.
Keywords: (13)CD(3) OH; far-infrared lasers; terahertz lasers